Effects of clinical parameters on patient‐reported outcome in cataract patients: a multicentre study. Issue 6 (25th March 2018) - Stolk‐Vos, Aline C.; Visser, Martijn S.; Klijn, Stijn; Timman, Reinier; Lansink, Peter; Nuijts, Rudy; Tjia, Khiun; Zijlmans, Bart; Kranenburg, Leonieke W.; Busschbach, Jan V.; Reus, Nicolaas J.
Abstract: Purpose: Ophthalmologists tend to evaluate the results of cataract surgery by focusing on the clinical visual and refractive outcomes and the incidence of complications, where patients' main interest might be their ability to perform daily activities. Therefore, there appears to be a need for optimizing effective communication between patients and ophthalmologist about the outcome of cataract surgery. The aim of this multicentre study was to determine the effects of whether the surgery was performed in one or two eyes, ocular comorbidity and per‐ and postoperative complications on visual function experienced by patients measured with the Catquest‐9SF. Methods: To measure patient‐reported outcomes, Catquest‐9SF data were collected between 2014 and 2015 in five Dutch hospitals. Data from 870 pairs of questionnaires – completed before and after cataract surgery – were compared with clinical data. Clinical data, retrieved from patients' medical files, consisted of one or two eye surgery, ocular comorbidity and per‐ and postoperative complications. Results: Quality of vision improved more in patients who had surgery in both eyes and had fewer postoperative complications (both p < 0.001). We found a nonsignificant trend that quality of vision was worse when ocular comorbidity was present. No significant effect of peroperative complications was observed. Conclusion: Our results emphasize the added value of the Catquest‐9SF as a tool for visual function experienced by patients; the additional information can complement clinical parameters to improve patient‐centred approaches in clinical practice.